La transición desde la delincuencia juvenil a la delincuencia adulta - Loeber, Rolf (Revista Española de Investigación Criminológica, 2011)
Researchers, professionals and the general public debate what leads young people to commit crimes. Some consider that there are "bad" people, already problematic since childhood, and that many of them later become persistent delinquents. Others, on the contrary, argue that juvenile delinquents are fundamentally a product of their environment: the worse their environment is, the worse their behavior over time. In 2009, the Study Group on the transition from juvenile delinquency to adult crime was created on the initiative of the National Institute of Justice of the United States Government (National Institute of Justice -NIJ- Study Group on Transitions from Juvenile Delinquency to Adult Crime) , who has developed [...]